Integrating AI and sustainability in technical and vocational education and training (TVET) - Azar, Ali Sorayyaei [Herausgeber]; Gupta, Shashi Kant [Herausgeber]; Hamed Taherdoost [Herausgeber]; Alhamaty, Fahima [Herausgeber] (IGI Global, 2025)
"Integrating AI and sustainability in technical and vocational education and training (TVET) provides a comprehensive guide on how TVET can successfully incorporate technological elements, addressing the frameworks, strategies, best practices, and challenges associated with this transformation. It supports educators in navigating the complexities of integrating AI and sustainability into vocational training. This book covers topics such as cybersecurity, data science, and supply chains, and is a useful resource for business owners, engineers, educators, academicians, researchers, and data scientists." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: G 2.2.1 Technologisierung; G 2.5 Nachhaltigkeit; G 2.2.2 Internet / Mediengesellschaft; 370; Künstliche Intelligenz; Nachhaltige Entwicklung; Berufsbildung; Technischer Fortschritt; Digitalkompetenz